Synergy of Digitalization and Sustainability: A Green Business Model for MSMES in the Era of Industry 5.0 - Hendra Purwanto; Handaru Indrian Sasmito Adi; Henny Sri Astuty; Suwarno Suwarno; Rohmat Rohmat; Shrafat Ali Sair (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2025)
Digital technological breakthroughs have transformed the way information is accessible and shared more rapidly in sectors including government, industry, and education. However, challenges such as misinformation and data privacy have also emerged. While digitalization in the economy drives platform-based growth, it also creates a digital divide and technological dependency. Micro, Small, and Medium Enterprises (MSMEs) are expected to implement innovative, creative, and sustainable business models in this context. This article explores the synergy between digitalization and sustainability in creating green business models for MSMEs in the Industry 5.0 era. MSMEs can improve operational efficiency, expand their markets, and play a role in building a sustainable economy by incorporating sustainability principles into their business strategies. Despite these challenges, strategic steps such as improving education and developing green technology infrastructure can help MSMEs overcome these obstacles. This study employed a qualitative approach with a descriptive model and a literature review method. Data were obtained through references to a collection of scientific journals and books published from 2023 to 2025. The analytical approach employed thematic analysis and data interpretation. The study's findings support the idea that combining sustainability and digitization is a smart way to work together and secure the long-term viability of MSMEs in Indonesia.